E-governance for good governance through public service delivery: an assessment of district e-service centres in Bangladesh - Salam, Mohammad Abdul (BRAC University, 2014)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2013.